2019
DOI: 10.1101/813121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Losing Control: Sleep Deprivation Impairs the Suppression of Unwanted Thoughts

Abstract: Unwanted memories often enter conscious awareness when we confront reminders.People vary widely in their talents at suppressing such memory intrusions; however, the factors that govern suppression ability are poorly understood. We tested the hypothesis that successful memory control requires sleep. Following overnight sleep or total sleep deprivation, participants attempted to suppress intrusions of emotionally negative and neutral scenes when confronted with reminders. The sleep-deprived group experienced sig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Hence, failure to suppress an unwanted memory when sleep deprived allows both the content and affective tone of that memory (represented by hippocampus and amygdala, respectively [2]) to intrude into consciousness, prompting a deterioration of emotional well-being. Supporting this view, whereas in well-rested people repeatedly suppressing thoughts about unpleasant images reduces subjective and psychophysiological arousal responses to those images, no such salutary benefit of memory suppression is observed in sleep-deprived individuals [7].…”
Section: Deficient Memory Control Undermines Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, failure to suppress an unwanted memory when sleep deprived allows both the content and affective tone of that memory (represented by hippocampus and amygdala, respectively [2]) to intrude into consciousness, prompting a deterioration of emotional well-being. Supporting this view, whereas in well-rested people repeatedly suppressing thoughts about unpleasant images reduces subjective and psychophysiological arousal responses to those images, no such salutary benefit of memory suppression is observed in sleep-deprived individuals [7].…”
Section: Deficient Memory Control Undermines Emotion Regulationmentioning
confidence: 99%
“…Recent work has demonstrated that sleep-deprived individuals are ineffective at suppressing unwanted thoughts [7]. Whereas memory suppression reduces future thought intrusions in well-rested people, sleep-deprived individuals fail to exhibit the same intrusion-reducing benefit of effective memory control.…”
Section: Sleep Loss Impairs Memory Controlmentioning
confidence: 99%
“… 14 For example, one previous event-related potentials (ERP) study found that poor sleep affects the speed to inhibit a motor response as well as the intensity of pre-motor inhibitory processes and task-relevant information processing, 15 while a more recent study found that sleep deprivation impairs memory control with sleep-deprived participants showing more unsuccessful suppression of intrusions of emotionally negative and neutral scenes than rested participants. 16 However, the effects of both total and partial sleep deprivation on inhibition control are not consistent. In TSD experiments, some studies have found that inhibition control is significantly diminished from baseline after TSD, 17–22 while others found no significant changes.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances escalate just before manic and depressive relapse in BD, and worsen during these episodes. 23 There is strong evidence detailing the negative effects of sleep disturbance on many aspects of cognition in healthy individuals 24 , including fragmented memory loss 25 and impaired suppression of unwanted thoughts 26 . Recently, evidence has emerged to suggest an association between sleep disturbance and cognitive impairment in mood disorders.…”
Section: Introductionmentioning
confidence: 99%